Intraoperative Neuropsychological assessment in brain tumors ressection located at eloquent areas - Is it ethical not considering "awake surgery"? - Holderbaum, Candice; Isolan, Gustavo (Clinical and Biomedical Research, 2014)
Brain tumors consist of a heterogeneous group of lesions with potential surgical morbidity when located in eloquente brain areas (motor area, language areas, visual areas, etc.) (1,6) Although intraoperative neurophysiological monitoring has the potential to decrease the risk of sequelae (hemiparesis/hemiplegia) in surgeries with the patient under general anesthesia (primary motor cortex and subcortical motor tract), this modern armamentarium cannot be used to map the speech (the patient is anesthetized). This is particularly important in a large group of patients with low-grade gliomas located in or aroud language areas.